Anti-DLBCL efficacy of DCZ0825 in vitro and in vivo: involvement of the PI3K‒AKT‒mTOR/JNK pathway. (2nd April 2021) - Hu, Ke; Li, Bo; Ma, Ruye; Yi, Hongfei; Xu, Zhijian; Peng, Yu; Yu, Dandan; Wu, Huiqun; Cheng, Taofang; Lu, Yumeng; Zhang, Yong; Wei, Rong; et al.
Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma, characterized by high heterogeneity. The poor outcome of a portion of patients who suffer relapsing or resistant to conventional treatment impels the development of novel agents for DLBCL. DCZ0825 is a novel compound derived from pterostilbene and osalmide, whose antitumor activities have drawn our attention. In this study, we found that DCZ0825 exhibited high cytotoxicity toward DLBCL cell lines in a dose- and time-dependent manner, as revealed by cell counting kit-8 assay. Flow cytometry and western blot analysis results showed that DCZ0825 also promoted cell apoptosis via both extrinsic and intrinsic apoptosis pathways mediated by caspase. In addition, DCZ0825 induced cell cycle arrest in the G2/M phase by downregulating Cdc25C, CDK1, and Cyclin B1, thus interfering with cell proliferation. Further investigation showed the involvement of the phosphatidylinositol 3-kinase (PI3K)‒AKT‒mTOR/JNK pathway in the efficacy of DCZ0825 against DLBCL. Remarkably, DCZ0825 also exerted notable cytotoxic effects in vivo as well, with low toxicity to important internal organs such as the liver and kidney. Our results suggest that DCZ0825 may have the potential to become a novel anti-DLBCL agent or to replenish the conventional therapeutic scheme of DLBCL.